KARAKTERISASI VARIASI MORFOLOGI Youngia japonica (L.) DC. (ASTERACEAE) DARI PULAU SUMATERA, INDONESIA - Anisatu Z. Wakhidah (Jurnal Pro-Life, 2019)
Youngia japonica (L.) DC. is perennial herb with yellow hermaphrodite flower. Based on herbarium collection from Herbarium Naturalis Biodiversity Centre (L), a variety was discovered from Japan in this species which named as Youngia japonica Benth var. acutiloba Miq. There are posibilites about discovering variety in herbarium collection of Youngia japonica (L.) DC. from Sumatera Island wich owned by Herbarium Bogoriense (BO). Fenetic analysis revealed that morphological character observation resulted 4 group with difference at some morphological characters in Youngia japonica (L.) DC herbarium. Those character were height of habit, stem surface, stipule, and leaf margin. Due to those character got great influenced by environment factor, those character not yet satisfy to classify Youngia japonica (L.) DC. in taxon infra species. Beside it, there is an assumption that Youngia japonica (L.) DC. has a large variety morphology which because of its adaptation ability. Keywords : herbarium, Sumatera, variety, Youngia japonica,